Reporting the Failure of Medical Devices - Kossovsky, N; Dujovny, M; Kossowsky, R (The New England journal of medicine, 1985)
To the Editor: Clinical failures of medical devices are a serious problem. Pacemaker leads that lose their insulation, 1 heart-valve prostheses that jam, 2 aneurysm clips that fracture, 3 and dialysis pumps that overheat 4 create life-threatening situations. Early and rapid identification of failed models, products, and production batches and dissemination of this knowledge are essential in order to protect the patient population at large. Two major information systems are available. Acting under the authority granted by the Medical Device Amendments of 1976, 5 the Food and Drug Administration, as of December 13, 1984, 6 requires manufacturers to report within five days the particulars of an . . . No extract is available for articles shorter than 400 words.